Treatment of Recurrent Ovarian Cysts and Primary Infertility by Iranian Traditional Medicine: A Case Report - Mehdi Salehi MD; Mohammad Setayesh MD; Roshanak Mokaberinejad MD, PhD (SAGE Publishing, 2017)
Infertility is a medical and psychosocial problem with a high prevalence. There are different treatments for this problem in Iranian traditional medicine. A 28-year-old woman presented with the complaints of 4 emergency operations of the left ovarian cyst during 4 years and infertility. Diagnostic laparoscopy showed an ovarian cyst, adhesion, and endometriosis. Hysteroscopy was unremarkable. After 2 months of letrozole administration, the ovarian cyst ruptured again. Considering the failure of conventional treatments, Iranian traditional medicine products were administered to the patient. After 3 months, the patient conceived and delivered a healthy boy through normal vaginal delivery. These compounds may help with pregnancy as a uterine tonic, vitalizer, and aphrodisiac with brain and cardiac tonic properties.